The full set is;
(x + 7) (3x + 1) = 3x² + 22x + 7
This question introduces the concept of polynomial long division.
This is what we are
Given: (3x² + 22x + 7) ÷ (x + 7) = 3x + 1
Now, from the concept of polynomial long division, we can see that:
if, f (x) ÷ g (x) = h (x),
This means that we can write:
f (x) = g (x) × h (x)
Applying the same concept to the question, we can also say:
(3x² + 22x + 7) ÷ (x + 7) = 3x + 1,
Next; (x + 7) (3x + 1) = 3x² + 22x + 7
Read more about polynomials at; brainly.com/question/12520197
#SPJ4